The Influence of Job Satisfaction on Employee Performance with Competency as A Mediation Variable at BPJS Ketenagakerjaan Branch Medan Raya - Fransiska Fransiska; Kiki Farida Ferine (International Journal of Economics, Management and Accounting (IJEMA), 2023)
This research is to look at the influence of Job Satisfaction on Employee Performance and Job Satisfaction on Competence and see whether competence indirectly influences Job Satisfaction and Employee Performance. This research method is to determine research results. The type of research used was associative quantitative, where the research was carried out at BPJS Employment throughout Medan Raya, the population used was 130 employees and was reduced to a sample using the Slovin technique to obtain a sample of 96 employees, the data collection techniques used were questionnaires and surveys. The results of this research are Based on the results of research that has been carried out and data analysis as explained in the previous chapter, The following conclusions from the research results are presented as follows: Job Satisfaction has a positive and significant effect on Employee Performance. This can be proven by the Path Coefficients table, the Original Sample value is 0.372 and the p value is 0.000 < 0.05. Job Satisfaction has a positive and significant effect on Competency. This can be proven by the Path Coefficients table, the Original Sample value is 0.865 and the p value is 0.000 < 0.05. Competence has a positive and significant effect on employee performance. This can be proven by the Path Coefficients table, the Original Sample value is 0.559 and the p value is 0.000 < 0.05.